TECHNOLOGICAL ASPECTS OF PROCESSING OF EDIBLE MUSSELS,CLAMS AND CRABS 1:SPOILAGE DURING DURING ICE STORAGE - CHINNAMMA, p L; CHAUDHURY, 0, R.; PILLAI, V K (Fishery Technology, 2025)
Rate and pattern of spoilage of some of the economicallyimportant edible species of shell fishes viz; Mytilus edulis (Mussel),Villorita cornucopia (Clam), Neptunus pelagicus (Crab) and Scyllaserrala (Crab) have been discussed in this communication. Chemicalindices used for objective evaluation of quality were water extractablenitrogen (WEN), non~protein nitrogen (NPN), free oe-amino nitrogen( o